Effect of Ultrasonic Pretreatment on the Yield and Antioxidant Property of Salvia nemorosa - Saeed Mollaei; Parisa Koutahi; Poopak Farnia (Biomedical and Biotechnology Research Journal)
Background: Salvia nemorosa L., belonging to the Lamiaceae family, has been widely studied due to its diverse biological activities. The essential oil (EO) of this plant has gained significant importance in pharmaceutical sciences and biotechnology due to its remarkable therapeutic potential. Methods: This study focuses on optimizing extraction methods using ultrasonic pretreatment prior to hydrodistillation (UAHD) to enhance extraction yield. The optimization of yield was performed through Box–Behnken Design and Response Surface Methodology (RSM) using three variables: ultrasonic time, ultrasonic power, and plant/liquid ratio. Results: Based on the RSM results, the highest EO yield was obtained with 35.5 min of ultrasonic time, 32.8°C of ultrasonic temperature, and a plant/liquid ratio of 30/451.8 g/mL, during 3 h of hydrodistillation (HD). The results indicated that the UAHD method produced the highest EO yield (0.73%) for S. nemorosa compared to the HD method, which yielded 0.2%. The study of the biological properties, including antioxidant activity, of EOs extracted from two methods (UAHD and HD) from S. nemorosa showed that the EO obtained from the UAHD method exhibited 20.60% higher antioxidant activity compared to the oil extracted by the HD method. These results indicate the superiority of the UAHD method in preserving and enhancing the antioxidant properties of the EO. Conclusions: Using ultrasonic pretreatment, as an environmentally friendly method, resulted in increased EO extraction yield and improved its biological activity compared to the HD method.